MicroRNA‐410 promotes cell proliferation by targeting BRD7 in non‐small cell lung cancer. Issue 17 (3rd July 2015) - Li, Dengrui; Yang, YongHui; Zhu, GuiYun; Liu, XinYan; Zhao, Min; Li, XiaoXia; Yang, QinOu
Abstract : miR‐410 acts as an oncogene or tumor suppressor gene in some malignancies. However, its role in NSCLC is still unknown. In this study, we showed that the expression of miR‐410 was up‐regulated in both human NSCLC tissues and cells. Overexpression of miR‐410 promoted cell proliferation, migration, and invasion of NSCLC. In addition, bromodomain‐containing protein 7 (BRD7) was a direct target of miR‐410. MiR‐410‐mediated downregulation of BRD7 led to increase Akt phosphorylation. Inhibition of Akt phosphorylation can rescue the effect of miR‐410 on NSCLC cell. The expression of BRD7 was downregulated in NSCLC and was inversely expressed with miR‐410 in NSCLC. Our data provided new knowledge regarding the role of miR‐410 in the lung cancer progression. Abstract : miR‐410 expression is increased in non‐small cell lung cancer. miR‐410 promoted non‐small cell lung cancer cells proliferation and invasion. miR‐410 inhibitor inhibited non‐small cell lung cancer cells proliferation and invasion. BRD7 is the direct target for miR‐410. miR‐410 induces cell proliferation in the AKT‐dependent pathway.